(untitled) (INNOVATIVE ECONOMY, 2019)
Trachenko L.A. FACTORS OF INFLUENCE ON THE FORMATION AND FUNCTIONING OF QUALITY MANAGEMENT SYSTEMS OF ENTERPRISES IN THE FIELD OF ENGINEERING SERVICES Purpose. The aim of the article is substantiation of the factors influencing the formation and functioning of quality management systems of enterprises in the field of engineering services. Methodology of research. The methods of analysis and synthesis, systematization, theoretical generalization and experimental have been used to investigate the issues of formation of quality management systems of enterprises of the field of engineering services of energy direction in the context of the requirements of ISO 9001: 2015; graphic – for visual presentation of factors that influence the formation and functioning of quality management systems of enterprises in the field of engineering. Findings. It is established that the formation and implementation of quality management systems in the context of the requirements of the international standard ISO 9001: 2015 at enterprises of the field of engineering services is an effective means of improving the quality of work (services), ensuring the competitiveness and development of companies, achievement of key business goals. It is proved that an important aspect in the formation and implementation of QMS of engineering enterprises is their integration into the company management system. The influence of internal and external factors on the formation and functioning of quality management systems of engineering enterprises as a means of reducing risks, improving the performance of companies and meeting the needs of their stakeholders is substantiated. Originality. The substantiation of the influence of internal and external factors on the formation and functioning of the QMS of engineering enterprises and on their management system has been further developed. Practical value. The analysis of the influence of internal and external factors on the formation and functioning of quality management systems in the context of requirements of the international standard ISO 9001: 2015 of enterprises in the field of engineering services makes it possible to reduce the level of uncertainty and risks in the processes of the companies’ activities, to improve the quality of work (services) and to maintain competitive positions. Key words: engineering services; quality management systems; international standard ISO 9001: 2015; internal and external factors of influence.